EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF DALAM MENINGKATKAN PEMAHAMAN SISWA TERHADAP KONSEP-KONSEP IPS DI SEKOLAH MENENGAH PERTAMA - Habryanto Abdullah (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2024)
This literature study aims to evaluate the effectiveness of cooperative learning models in improving students' understanding of Social Studies (IPS) concepts in Junior High Schools (SMP). Cooperative learning methods that involve students working together in small groups are often considered to be able to improve student engagement and understanding compared to traditional learning methods that are more frontal and individualistic. This study reviews a number of relevant literatures, including journals, articles, and empirical studies that focus on the use of cooperative learning models in IPS education. The results of the study indicate that cooperative learning models, such as Jigsaw, Think-Pair-Share, and Group Investigation, can significantly improve the understanding of IPS concepts. These models support the exchange of ideas, in-depth discussions, and better reflection among students, which are important factors in the IPS learning process. In addition, cooperative learning also creates a more supportive and interactive learning environment, which can provide better opportunities for students to understand abstract and complex concepts in IPS. However, the study also identified several challenges, such as the need for more time in preparation and implementation, and the need for adequate teacher training to implement this learning model effectively. Based on the results of this study, it is recommended that schools at the junior high school level consider integrating cooperative learning models into their social studies curriculum to enhance effective student understanding and build important social skills as part of the learning process.